Lung metastasectomy following kidney tumors: outcomes and prognostic factors from a single-center experience - Meacci, Elisa (J Thorac Dis, 2017)
BACKGROUND: The lung is one of the sites most frequently affected by metastatic renal cell carcinoma (mRCC). Nonsurgical therapy for mRCC has limited efficacy, while the 5-year survival rates data published in literature after pulmonary surgery for metastasectomy, emphasize the role of surgery as the treatment that guarantees the best effectiveness in pulmonary resectable metastases. METHODS: From January 2000 to March 2016, 27 patients underwent pulmonary metastasectomy for metastatic renal cancer was retrospectively reviewed. Primary renal cancer was controlled in all patients and there was no other metastatic site in addition to the lung, at the time of metastasectomy. The aim of the study was to identify outcomes and prognostic factors in association with survival after complete pulmonary resection of metastases in a subgroup of patients with isolated pulmonary metastases from RCC. RESULTS: Five- and 10-year overall survival (OS) from first pulmonary metastasectomy was 75% and 59%, respectively. Independent prognostic factor influencing survival were: dimension of pulmonary metastases ≥2 cm (3-year survival: 67% vs. 100%; P=0.014) and disease free interval (DFI) ≥5 years (3-year survival: 94% vs. 28%; P=0.05). The only independent prognostic factors affecting DFI was the dimension of pulmonary metastases ≥2 cm (5-year DFI: 67% vs. 89%; P=0.03) at univariate analysis. CONCLUSIONS: Considering the good results based on high long-term efficacy and low morbidity after metastases surgical resection, we always recommend metastasectomy in patients with technically resectable metastases, especially in case of long DFI and reduced dimension of pulmonary lesions.